Protective coating with stealth function and preparation method thereof
By using a three-dimensional conductive network formed by combining a matrix resin with an MXene dispersion, and combining it with a conductive polymer coating layer, the problems of molding complexity and wide-band wave absorption performance of integrated materials for heat protection/insulation and stealth have been solved, achieving high strength, toughness and wide-band electromagnetic wave absorption.
Patent Information
- Application Number
- CN202510475590.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-04-16
AI Technical Summary
Existing heat-insulating and stealth integrated materials are difficult to mold in one piece and have wide-band wave absorption performance, and the molding process is complex, which cannot meet the high requirements of modern electromagnetic detection technology.
A composition containing a matrix resin, stealth filler, flame retardant, fiber filler, additives and curing agent is used. During the preparation process, amino silicone compounds are introduced to form a high cross-linking density network structure, which is then compounded with MXene dispersion to form a three-dimensional conductive network. Combined with a conductive polymer coating layer, broadband electromagnetic wave absorption is achieved.
The material achieves high strength, toughness, and impact resistance, while also possessing wide-band electromagnetic wave absorption capabilities, meeting the comprehensive performance requirements of modern electromagnetic detection technology.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of stealth material preparation, in particular to a protective coating with a stealth function and a preparation method thereof. BACKGROUND
[0002] With the rapid development of modern electromagnetic detection technology, various types of equipment are facing the dual challenges of aerodynamic heating, high-speed scouring and multi-band electromagnetic detection, and higher requirements are put forward for the comprehensive performance of surface protective materials. An ideal protective material needs to have excellent ablation resistance, efficient heat insulation, lightweight, high shear resistance, and also needs to realize wide-band stealth and wave absorption functions, and meet the engineering application requirements of room temperature curing, convenient construction and strong environmental adaptability, so the integration of heat protection and stealth has become the core development direction of protective coatings.
[0003] Chinese Patent CN109532143A discloses a heat protection and stealth integrated skin and a preparation method thereof, which is characterized by being formed by a plurality of layers of materials connected by bolts from the outside to the inside, and the disadvantage is that the materials are not integrally formed, and the forming process is complex. Chinese Patent CN117106372A discloses a coating with stealth, heat insulation and heat protection functions, which is characterized by a self-made core-shell hollow filler that plays a role in dissipating electromagnetic wave energy, but the disadvantage is that it only supports 10-12GHz frequency wave absorption performance, and the curing period is long. In summary, the current heat protection and stealth integrated material cannot solve the problems of integrated forming and wide-band wave absorption performance. In view of the above shortcomings and application requirements, it is urgent to develop a new type of stealth coating that is compatible with multiple bands, environmentally adaptive and green and efficient, to break through the limitations of the existing technology and meet the protection needs of future battlefield and civilian high-end equipment. SUMMARY
[0004] In order to solve the technical problems mentioned in the background art, the application provides a protective coating with a stealth function and a preparation method thereof.
[0005] In a first aspect, the application provides a protective coating with a stealth function, which adopts the following technical solution:
[0006] A protective coating with a stealth function comprises the following raw materials by weight: 60-80 parts of base resin, 20-40 parts of stealth filler, 5-10 parts of flame retardant, 8-10 parts of fiber filler, 3-8 parts of auxiliary agent, 3-5 parts of curing agent and 40-50 parts of solvent.
[0007] Preferably, the preparation step of the base resin is as follows: the epoxy resin and the amino silicon compound are added to toluene, stirred uniformly, heated to 60-80 DEG C, a catalyst is added, stirred for 2-4 h, and vacuum dried to obtain the base resin.
[0008] Preferably, the mass ratio of the epoxy resin, amino silicon compound and toluene is 2-3:0.5-1:5-10.
[0009] Preferably, the amino silicon compound is composed of N-phenyl-3-aminopropyl trimethoxysilane and aminopropyl-terminated polydimethylsiloxane in a mass ratio of 1-3:10-12.
[0010] Preferably, the catalyst is added in an amount of 0.1-1% of the mass sum of the epoxy resin and the amino silicon compound.
[0011] Preferably, the preparation of the stealth filler comprises the following steps:
[0012] Step 1, disperse titanium aluminum carbide in HF solution, etch for 24-48h at a temperature of 25-30℃, ultrasonic dispersion, centrifugal separation, take the supernatant, and obtain MXene dispersion;
[0013] Step 2, mix the conductive polymer monomer with the MXene dispersion, adjust the pH to 2-3, add ammonium persulfate, stir and react under nitrogen protection at a temperature of 5-10℃ for 2-3h, add p-phenylenediamine, heat to 20-30℃, continue to stir and react for 3-5h, precipitate, wash and dry to obtain a conductive composite;
[0014] Step 3, disperse zinc nitrate and cerium nitrate in ethylene glycol in a molar ratio of 1-1.2:2-3, react at 180-200℃ for 12-14h, filter, wash and dry to obtain core-shell structure particles;
[0015] Step 4, mix the conductive composite and the core-shell structure particles in a mass ratio of 10-12:3-4 to obtain the stealth filler.
[0016] Preferably, the mass ratio of the conductive polymer monomer, the MXene dispersion, ammonium persulfate and p-phenylenediamine in step 2 is 4-5:10-12:0.1-0.4:0.5-1.
[0017] Preferably, the conductive polymer monomer in step 2 is composed of 3,4-vinyl dithiophene and N-amino-2-cyanopyrrole in a mass ratio of 5-8:1-3.
[0018] Preferably, the flame retardant is one or more of aluminum hydroxide, magnesium hydroxide, magnesium oxide and zinc borate.
[0019] Preferably, the fiber filler is one or more of chopped high silica fiber, chopped glass fiber, chopped quartz fiber and mullite fiber.
[0020] Preferably, the auxiliary agent is one or more of a coupling agent, a leveling agent and a defoaming agent.
[0021] Preferably, the curing agent is an epoxy resin curing agent.
[0022] Preferably, the solvent is a mixture of xylene and butanone in a volume ratio of 7:3.
[0023] In a second aspect, the application also provides a preparation method of the protective coating with the stealth function, which adopts the following technical scheme:
[0024] The preparation method of the protective coating with the stealth function comprises the following preparation steps:
[0025] (1) Pre-mix and disperse the base resin, the flame retardant, the fiber filler, the auxiliary agent, and 1 / 2-2 / 3 volume of the solvent to obtain component A;
[0026] (2) Pre-mix and disperse the stealth filler, the curing agent, and the remaining solvent to obtain component B;
[0027] (3) Mix the component A and the component B uniformly to obtain the protective coating with the stealth function.
[0028] In the process of preparing the base resin, two kinds of amino silicon compounds are introduced into the epoxy resin. The N-phenyl-3-aminopropyl trimethoxysilane contains phenyl and amino groups, and the amino groups thereof react with the epoxy resin rapidly to form a rigid network with high cross-linking density, thereby improving the strength and heat resistance of the material. The methoxysilane groups hydrolyze to generate silicon hydroxyl groups (Si-OH), which can enhance the interfacial bonding force with the inorganic filler. The long-chain flexible siloxane main chain (-Si-O-Si-) acts as a "soft segment" and is dispersed in the resin matrix, which significantly improves the flexibility and impact resistance of the material, avoids brittle fracture caused by pure rigid cross-linking, and the combination of the two makes the base resin have high strength and certain toughness.
[0029] The N-phenyl-3-aminopropyl trimethoxysilane as a small molecule silane can rapidly diffuse to the surface of the filler, improve the interfacial bonding between the resin and the filler through chemical bonds (such as Si-O-inorganic surface), and reduce interfacial defects. The long-chain polysiloxane acts as a "compatibilizer", and the hydrophobic siloxane segment thereof forms a micro-phase separation structure with the polar groups of the epoxy resin, but the reaction of the terminal amino group with the epoxy group can inhibit macro-phase separation, thereby improving the uniformity and processing stability of the resin system. Small molecules strengthen the interface, and macromolecules stabilize the matrix, and the two synergistically reduce the internal stress of the material. In addition, the two kinds of amino silicon compounds can cross-link with the epoxy resin to form a dense network structure, thereby improving the chemical corrosion resistance.
[0030] In the process of preparing the stealth filler, MXene dispersion liquid is obtained by over-etching titanium aluminum carbide, the MXene dispersion liquid has high conductivity and rich surface functional groups (-OH, -F, etc.), after in-situ compounding with conductive polymers, a three-dimensional conductive network is formed, through dielectric loss and interface polarization effect, electromagnetic wave energy is efficiently dissipated, the copolymer of 3,4-vinyl dioxothiophene and N-amino-2-cyanopyrrole can adjust the polarization relaxation frequency through molecular structure design, broaden the wave absorption frequency band, 3,4-vinyl dioxothiophene provides high conductivity, the amino functional group of N-amino-2-cyanopyrrole can form a hydrogen bond with the -OH on the surface of MXene, and the stability of the composite is improved, the strong polarity of the cyano group (-CN) induces dipole polarization, and the dielectric loss is enhanced. First, 3,4-vinyl dioxothiophene and N-amino-2-cyanopyrrole are introduced, then p-phenylenediamine is introduced, and a stable polymer coating layer is formed, which enhances the interface bonding between MXene and the polymer and avoids the breakage of the conductive network. The prepared core-shell structure has dielectric loss and magnetic loss, and through the magnetic-electric synergistic effect, the synergistic effect of the conductive network (MXene / polymer) is enhanced, and wide-band electromagnetic wave absorption is realized. DETAILED DESCRIPTION
[0031] The application will be further described in detail below in combination with examples.
[0032] The epoxy resin (model number: E51) used in the examples and comparative examples of the application was purchased from Jinan Zesheng Chemical Co., Ltd.; N-phenyl-3-aminopropyl trimethoxysilane was purchased from Jingzhou Yinjie Chemical Co., Ltd.; polydimethylsiloxane capped with an aminopropyl group (product number: 9841121) was purchased from Hubei Jiufenglong Chemical Co., Ltd.; 3,4-vinyl dioxothiophene (model number: PZ541321) was purchased from Jining Tangyi Chemical Co., Ltd.; N-amino-2-cyanopyrrole was purchased from Jiangsu Lein Environmental Protection Technology Co., Ltd.; an epoxy resin curing agent (model number: SH-200-201) was purchased from Guangzhou Xinxili Metallurgical Chemical Co., Ltd.; and short-cut glass fibers (model number: BLSX-2) were purchased from Shijiazhuang Wende Mineral Products Co., Ltd.
[0033] Examples 1-3 provide a protective coating with a stealth function and a preparation method thereof.
[0034] Example 1
[0035] A protective coating with a stealth function comprises the following raw materials by weight: 60 parts of a matrix resin, 20 parts of a stealth filler, 5 parts of a flame retardant, 8 parts of a fibrous filler, 3 parts of an additive, 3 parts of a curing agent, and 40 parts of a solvent, wherein the flame retardant is aluminum hydroxide, the fibrous filler is short-cut glass fiber, the additive is silane coupling agent KH-550, the curing agent is an epoxy resin curing agent, and the solvent is a mixture of dimethylbenzene and butanone in a volume ratio of 7:3.
[0036] The preparation steps of the base resin are as follows: the epoxy resin and the amino silicon compound are added to toluene, stirred uniformly, the stirring speed is 200 rpm, stirring for 10 min, the temperature is raised to 60 DEG C, the dibutyl tin dilaurate is added, stirring for 2 h, the vacuum degree is 0.03 MPa at 50 DEG C, vacuum drying for 10 h, and the base resin is obtained, wherein the mass ratio of the epoxy resin, the amino silicon compound and the toluene is 2:0.5:5, the amino silicon compound is composed of N-phenyl-3-aminopropyl trimethoxysilane and aminopropyl-terminated polydimethylsiloxane with a mass ratio of 1:10, and the addition amount of the dibutyl tin dilaurate is 0.1% of the mass sum of the epoxy resin and the amino silicon compound.
[0037] The preparation of the stealth filler includes the following steps:
[0038] Step 1, dispersing titanium aluminum carbide in a 10wt% HF solution, etching for 24 h at a temperature of 25 DEG C, ultrasonic dispersion, ultrasonic power is 100 W, ultrasonic frequency is 40 KHz, centrifugal separation, centrifugal speed is 4000 rpm, centrifugal separation for 5 min, taking the supernatant, and obtaining MXene dispersion, wherein the mass ratio of titanium aluminum carbide and the HF solution is 1:10;
[0039] Step 2, mixing the conductive polymer monomer with the MXene dispersion, adjusting the pH to 2, adding ammonium persulfate, stirring for 2 h at a temperature of 5 DEG C under nitrogen protection, the stirring speed is 200 rpm, adding p-phenylenediamine, raising the temperature to 20 DEG C, and continuing to stir for 3 h, then precipitating, deionized water washing for 3 times, and drying at a temperature of 40 DEG C for 18 h to obtain the conductive composite, wherein the mass ratio of the conductive polymer monomer, the MXene dispersion, the ammonium persulfate and the p-phenylenediamine is 4:10:0.1:0.5, and the conductive polymer monomer is composed of 3,4-vinyl dioxothiophene and N-amino-2-cyanopyrrole with a mass ratio of 5:1;
[0040] Step 3, dispersing zinc nitrate and cerium nitrate in ethylene glycol according to a molar ratio of 1:2, wherein the amount of ethylene glycol is 5 times of the total mass of zinc nitrate and cerium nitrate, transferring to a high-pressure reaction kettle, reacting at 180 DEG C for 12 h, filtering, deionized water washing for 3 times, and drying at 60 DEG C for 8 h to obtain the core-shell structure particles;
[0041] Step 4, mixing the conductive composite and the core-shell structure particles according to a mass ratio of 10:3 to obtain the stealth filler.
[0042] A preparation method of a protective coating with a stealth function, including the following steps:
[0043] (1) The base resin, flame retardant, fiber filler, additive and 1 / 2 volume of solvent are stirred at a speed of 200 rpm for 20 min, and then stirred at a speed of 800 rpm for 30 min to pre-mix and disperse, to obtain component A;
[0044] (2) The stealth filler, curing agent and remaining solvent are stirred at a speed of 800 rpm for 20 min to pre-mix and disperse, to obtain component B;
[0045] (3) The components A and B are mixed uniformly at a stirring speed of 500 rpm for 30 min to obtain the protective coating with stealth function.
[0046] Example 2
[0047] A protective coating with stealth function, comprising the following raw materials by weight: base resin 70 parts, stealth filler 30 parts, flame retardant 8 parts, fiber filler 9 parts, additive 5 parts, curing agent 4 parts, and solvent 45 parts, wherein the flame retardant is aluminum hydroxide, the fiber filler is chopped glass fiber, the additive is silane coupling agent KH-550, the curing agent is epoxy resin curing agent, and the solvent is a mixture of dimethylbenzene and butanone in a volume ratio of 7:3.
[0048] The preparation steps of the base resin are as follows: the epoxy resin and amino silicon compound are added to toluene, stirred uniformly, then stirred at a speed of 250 rpm for 15 min, heated to 70℃, then dibutyltin dilaurate is added, stirred for 3 h, vacuum dried at 55℃ and a vacuum degree of 0.05 MPa for 11 h to obtain the base resin, wherein the mass ratio of the epoxy resin, amino silicon compound and toluene is 2.5:0.8:8, the amino silicon compound is composed of N-phenyl-3-aminopropyl trimethoxysilane and aminopropyl-terminated polydimethylsiloxane in a mass ratio of 2:11, and the addition amount of dibutyltin dilaurate is 0.5% of the mass sum of the epoxy resin and amino silicon compound.
[0049] The preparation of the stealth filler includes the following steps:
[0050] Step 1, disperse titanium aluminum carbide in a 15wt% HF solution, etch at a temperature of 28℃ for 36 h, ultrasonic dispersion, ultrasonic power 200 W, ultrasonic frequency 50 KHz, centrifugal separation, centrifugal speed 4500 rpm, centrifugal for 8 min, take the supernatant, to obtain MXene dispersion, wherein the mass ratio of titanium aluminum carbide and HF solution is 2:10;
[0051] Step 2, mix the conductive polymer monomer with the MXene dispersion liquid, adjust the pH to 2.5, add ammonium persulfate, stir under nitrogen protection at a temperature of 8℃ for 2.5h, the stirring speed is 250rpm, add p-phenylenediamine, heat to 25℃, continue to stir for 4h, after precipitation separation and deionized water washing for 3 times, dry at a temperature of 50℃ for 21h, to obtain the conductive composite, wherein the mass ratio of the conductive polymer monomer, the MXene dispersion liquid, the ammonium persulfate and the p-phenylenediamine is 4.5:11:0.25:0.8, the conductive polymer monomer is composed of 3,4-vinyldioxylthiophene and N-amino-2-cyanopyrrole with a mass ratio of 7:2;
[0052] Step 3, disperse zinc nitrate and cerium nitrate in ethylene glycol according to a molar ratio of 1.1:2.5, wherein the amount of ethylene glycol is 8 times the total mass of zinc nitrate and cerium nitrate, transfer to a high-pressure reaction kettle, react at 190℃ for 13h, filter, deionized water washing for 3 times, dry at 70℃ for 10h, to obtain the core-shell structure particles;
[0053] Step 4, mix the conductive composite and the core-shell structure particles according to a mass ratio of 11:3.5, to obtain the stealth filler.
[0054] A preparation method of a protective coating with stealth function, comprising the following steps:
[0055] (1) Pre-mix and disperse the base resin, the flame retardant, the fiber filler, the auxiliary agent and 3 / 5 volume of solvent at a stirring speed of 250rpm for 25min, and then at a stirring speed of 900rpm for 35min, to obtain component A;
[0056] (2) Pre-mix and disperse the stealth filler, the curing agent and the remaining solvent at a stirring speed of 900rpm for 30min, to obtain component B;
[0057] (3) Mix component A and component B uniformly at a stirring speed of 600rpm for 35min, to obtain the protective coating with stealth function.
[0058] Example 3
[0059] A protective coating with stealth function, comprising the following raw materials by weight: base resin 80 parts, stealth filler 40 parts, flame retardant 10 parts, fiber filler 10 parts, auxiliary agent 8 parts, curing agent 5 parts, and solvent 50 parts, wherein the flame retardant is aluminum hydroxide, the fiber filler is chopped glass fiber, the auxiliary agent is silane coupling agent KH-550, the curing agent is epoxy resin curing agent, and the solvent is a mixture of dimethylbenzene and butanone with a volume ratio of 7:3.
[0060] The preparation steps of the base resin are as follows: the epoxy resin and the amino silicon compound are added to toluene, stirred uniformly, the stirring speed is 300 rpm, stirring for 20 min, the temperature is raised to 80 DEG C, the dibutyl tin dilaurate is added, stirring for 4 h, the vacuum degree is 0.1 MPa at 60 DEG C, vacuum drying for 12 h, and the base resin is obtained, wherein the mass ratio of the epoxy resin, the amino silicon compound and the toluene is 3:1:10, the amino silicon compound is composed of N-phenyl-3-aminopropyl trimethoxysilane and aminopropyl-terminated polydimethylsiloxane with a mass ratio of 3:12, and the addition amount of the dibutyl tin dilaurate is 1% of the mass sum of the epoxy resin and the amino silicon compound.
[0061] The preparation of the stealth filler includes the following steps:
[0062] Step 1, titanium aluminum carbide is dispersed in a 20wt% HF solution, etching for 48 h at a temperature of 30 DEG C, ultrasonic dispersion, ultrasonic power is 300 W, ultrasonic frequency is 60 KHz, centrifugal separation, centrifugal speed is 5000 rpm, centrifugal separation for 10 min, taking the supernatant, and obtaining a MXene dispersion, wherein the mass ratio of titanium aluminum carbide and the HF solution is 3:10;
[0063] Step 2, the conductive polymer monomer is mixed with the MXene dispersion, the PH is adjusted to 3, ammonium persulfate is added, stirring for 3 h under nitrogen protection at a temperature of 10 DEG C, the stirring speed is 300 rpm, p-phenylenediamine is added, the temperature is raised to 30 DEG C, and the stirring is continued for 5 h, then the precipitate is separated and washed with deionized water for 3 times, and the conductive composite is obtained by drying at a temperature of 60 DEG C for 24 h, wherein the mass ratio of the conductive polymer monomer, the MXene dispersion, the ammonium persulfate and the p-phenylenediamine is 5:12:0.4:1, and the conductive polymer monomer is composed of 3,4-vinyl dioxothiophene and N-amino-2-cyanopyrrole with a mass ratio of 8:3;
[0064] Step 3, zinc nitrate and cerium nitrate are dispersed in ethylene glycol according to a molar ratio of 1.2:3, wherein the amount of ethylene glycol is 10 times the total mass of zinc nitrate and cerium nitrate, transferred to a high-pressure reaction kettle, reacted at 200 DEG C for 14 h, filtered, washed with deionized water for 3 times, and dried at 80 DEG C for 12 h to obtain core-shell structure particles;
[0065] Step 4, the conductive composite and the core-shell structure particles are mixed according to a mass ratio of 12:4 to obtain the stealth filler.
[0066] A preparation method of a protective coating with a stealth function, comprising the following steps:
[0067] (1) The base resin, flame retardant, fiber filler, additive and 2 / 3 volume of solvent are stirred at a speed of 300 rpm for 30 min, and then stirred at a speed of 1000 rpm for 40 min to pre-mix and disperse, to obtain component A;
[0068] (2) The stealth filler, curing agent and remaining solvent are stirred at a speed of 1000 rpm for 40 min to pre-mix and disperse, to obtain component B;
[0069] (3) The components A and B are mixed uniformly at a stirring speed of 800 rpm for 40 min to obtain the protective coating with stealth function.
[0070] Comparative Example 1
[0071] A protective coating with stealth function comprises the following raw materials by weight: base resin 60 parts, stealth filler 20 parts, flame retardant 5 parts, fiber filler 8 parts, additive 3 parts, curing agent 3 parts, and solvent 40 parts. The flame retardant is aluminum hydroxide, the fiber filler is chopped glass fiber, the additive is silane coupling agent KH-550, the curing agent is epoxy resin curing agent, and the solvent is a mixture of dimethylbenzene and butanone in a volume ratio of 7:3.
[0072] The base resin is prepared by the following steps: epoxy resin and N-phenyl-3-aminopropyl trimethoxysilane are added to toluene, stirred uniformly, then stirred at a speed of 200 rpm for 10 min, heated to 60℃, dibutyltin dilaurate is added, stirred for 2 h, vacuum dried at 50℃ and a vacuum degree of 0.03 MPa for 10 h to obtain the base resin. The mass ratio of epoxy resin, N-phenyl-3-aminopropyl trimethoxysilane and toluene is 2:0.5:5, and the addition amount of dibutyltin dilaurate is 0.1% of the mass of the epoxy resin and N-phenyl-3-aminopropyl trimethoxysilane.
[0073] The preparation of the stealth filler includes the following steps:
[0074] Step 1: titanium aluminum carbide is dispersed in a 10wt% HF solution, etched at a temperature of 25℃ for 24 h, ultrasonically dispersed at a power of 100 W and a frequency of 40 KHz, centrifuged at a speed of 4000 rpm for 5 min, and the supernatant is taken to obtain an MXene dispersion. The mass ratio of titanium aluminum carbide to HF solution is 1:10.
[0075] Step 2, mix the conductive polymer monomer with the MXene dispersion liquid, adjust the pH to 2, add ammonium persulfate, stir under nitrogen protection at a temperature of 5℃ for 2h, stir at a speed of 200rpm, add p-phenylenediamine, heat to 20℃, continue to stir for 3h, precipitate, deionized water wash 3 times, dry at a temperature of 40℃ for 18h to obtain the conductive composite, wherein the mass ratio of the conductive polymer monomer, the MXene dispersion liquid, the ammonium persulfate and the p-phenylenediamine is 4:10:0.1:0.5, and the conductive polymer monomer is composed of 3,4-vinyldioxylthiophene and N-amino-2-cyanopyrrole with a mass ratio of 5:1;
[0076] Step 3, disperse zinc nitrate and cerium nitrate in ethylene glycol according to a molar ratio of 1:2, wherein the amount of ethylene glycol is 5 times the total mass of zinc nitrate and cerium nitrate, transfer to a high-pressure reaction kettle, react at 180℃ for 12h, filter, deionized water wash 3 times, dry at 60℃ for 8h to obtain core-shell structure particles;
[0077] Step 4, mix the conductive composite and the core-shell structure particles according to a mass ratio of 10:3 to obtain the stealth filler.
[0078] A preparation method of a protective coating with a stealth function, comprising the following steps:
[0079] (1) Pre-mix and disperse the base resin, the flame retardant, the fiber filler, the auxiliary agent and 1 / 2 volume of solvent at a stirring speed of 200rpm for 20min, and then at a stirring speed of 800rpm for 30min to obtain component A;
[0080] (2) Pre-mix and disperse the stealth filler, the curing agent and the remaining solvent at a stirring speed of 800rpm for 20min to obtain component B;
[0081] (3) Mix component A and component B uniformly at a stirring speed of 500rpm for 30min to obtain the protective coating with a stealth function.
[0082] Comparative Example 2
[0083] A protective coating with a stealth function, comprising the following raw materials by weight: base resin 60 parts, stealth filler 20 parts, flame retardant 5 parts, fiber filler 8 parts, auxiliary agent 3 parts, curing agent 3 parts, and solvent 40 parts, wherein the flame retardant is aluminum hydroxide, the fiber filler is chopped glass fiber, the auxiliary agent is silane coupling agent KH-550, the curing agent is epoxy resin curing agent, and the solvent is a mixture of dimethylbenzene and butanone with a volume ratio of 7:3.
[0084] The preparation steps of the base resin are as follows: the epoxy resin and the aminopropyl-terminated polydimethylsiloxane are added into toluene, stirred uniformly, the stirring speed is 200 rpm, stirring for 10 min, the temperature is raised to 60 DEG C, dibutyltin dilaurate is added, stirring for 2 h, the vacuum degree is 0.03 MPa at 50 DEG C, vacuum drying for 10 h, and the base resin is obtained, wherein the mass ratio of the epoxy resin, the aminopropyl-terminated polydimethylsiloxane and the toluene is 2:0.5:5, and the addition amount of the dibutyltin dilaurate is 0.1% of the mass of the epoxy resin and the aminopropyl-terminated polydimethylsiloxane.
[0085] The preparation of the stealth filler comprises the following steps:
[0086] Step 1: titanium aluminum carbide is dispersed in a 10wt% HF solution, etching for 24 h at a temperature of 25 DEG C, ultrasonic dispersion, ultrasonic power is 100 W, ultrasonic frequency is 40 KHz, centrifugal separation, centrifugal speed is 4000 rpm, centrifugal separation for 5 min, taking the supernatant, and the MXene dispersion liquid is obtained, wherein the mass ratio of titanium aluminum carbide and the HF solution is 1:10;
[0087] Step 2: the conductive polymer monomer is mixed with the MXene dispersion liquid, the PH is adjusted to 2, ammonium persulfate is added, stirring for 2 h under nitrogen protection at a temperature of 5 DEG C, the stirring speed is 200 rpm, p-phenylenediamine is added, the temperature is raised to 20 DEG C, and the stirring is continued for 3 h, then the precipitate is separated and washed with deionized water for 3 times, and the conductive composite is obtained by drying at a temperature of 40 DEG C for 18 h, wherein the mass ratio of the conductive polymer monomer, the MXene dispersion liquid, the ammonium persulfate and the p-phenylenediamine is 4:10:0.1:0.5, and the conductive polymer monomer is composed of 3,4-vinyldioxothiophene and N-amino-2-cyanopyrrole at a mass ratio of 5:1;
[0088] Step 3: zinc nitrate and cerium nitrate are dispersed in ethylene glycol according to a molar ratio of 1:2, wherein the amount of ethylene glycol is 5 times of the total mass of zinc nitrate and cerium nitrate, transferred to a high-pressure reaction kettle, reacted at 180 DEG C for 12 h, filtered, washed with deionized water for 3 times, and dried at 60 DEG C for 8 h to obtain the core-shell structure particles;
[0089] Step 4: the conductive composite and the core-shell structure particles are mixed according to a mass ratio of 10:3 to obtain the stealth filler.
[0090] A preparation method of a protective coating with a stealth function, comprising the following steps:
[0091] (1) the base resin, the flame retardant, the fiber filler, the auxiliary agent and 1 / 2 volume of solvent are pre-mixed and dispersed at a stirring speed of 200 rpm for 20 min and then at a stirring speed of 800 rpm for 30 min to obtain component A;
[0092] (2) The stealth filler, curing agent and remaining solvent are pre-mixed and dispersed at a stirring speed of 800 rpm for 20 min to obtain component B;
[0093] (3) Components A and B are uniformly mixed at a stirring speed of 500 rpm for 30 min to obtain the protective coating with a stealth function.
[0094] Comparative Example 3
[0095] A protective coating with a stealth function comprises the following raw materials by weight: 60 parts of base resin, 20 parts of stealth filler, 5 parts of flame retardant, 8 parts of fiber filler, 3 parts of additive, 3 parts of curing agent, and 40 parts of solvent, wherein the flame retardant is aluminum hydroxide, the fiber filler is chopped glass fiber, the additive is silane coupling agent KH-550, the curing agent is epoxy resin curing agent, and the solvent is a mixture of dimethylbenzene and butanone in a volume ratio of 7:3.
[0096] The preparation steps of the base resin are as follows: epoxy resin and amino silicon compound are added to toluene, stirred uniformly, the stirring speed is 200 rpm, stirring for 10 min, the temperature is raised to 60℃, dibutyltin dilaurate is added, stirring for 2 h, vacuum drying at 50℃ and a vacuum degree of 0.03 MPa for 10 h, to obtain the base resin, the mass ratio of epoxy resin, amino silicon compound and toluene is 2:0.5:5, the amino silicon compound is composed of N-phenyl-3-aminopropyl trimethoxysilane and aminopropyl-terminated polydimethylsiloxane in a mass ratio of 1:10, and the addition amount of dibutyltin dilaurate is 0.1% of the mass sum of the epoxy resin and the amino silicon compound.
[0097] The preparation of the stealth filler includes the following steps:
[0098] Step 1, disperse titanium aluminum carbide in a 10wt% HF solution, etch at a temperature of 25℃ for 24 h, ultrasonic dispersion, ultrasonic power 100 W, ultrasonic frequency 40 KHz, centrifugal separation, centrifugal speed 4000 rpm, centrifugal for 5 min, take the supernatant, obtain MXene dispersion, wherein the mass ratio of titanium aluminum carbide to HF solution is 1:10;
[0099] Step 2, mix 3, 4-vinyl dioxothiophene with MXene dispersion liquid, adjust the pH to 2, add ammonium persulfate, stir under nitrogen protection at a temperature of 5℃ for 2h, add p-phenylenediamine, heat to 20℃, continue to stir for 3h, precipitate, deionized water wash 3 times, dry at a temperature of 40℃ for 18h to obtain the conductive composite, wherein the mass ratio of 3, 4-vinyl dioxothiophene, MXene dispersion liquid, ammonium persulfate and p-phenylenediamine is 4:10:0.1:0.5;
[0100] Step 3, disperse zinc nitrate and cerium nitrate in ethylene glycol according to a molar ratio of 1:2, wherein the amount of ethylene glycol is 5 times the total mass of zinc nitrate and cerium nitrate, transfer to a high-pressure reaction kettle, react at 180℃ for 12h, filter, deionized water wash 3 times, dry at 60℃ for 8h to obtain core-shell structure particles;
[0101] Step 4, mix the conductive composite and the core-shell structure particles according to a mass ratio of 10:3 to obtain the stealth filler.
[0102] A preparation method of a protective coating with a stealth function, comprising the following steps:
[0103] (1) Pre-mix and disperse the base resin, the flame retardant, the fiber filler, the auxiliary agent and 1 / 2 volume of solvent at a stirring speed of 200rpm for 20min, and then at a stirring speed of 800rpm for 30min to obtain component A;
[0104] (2) Pre-mix and disperse the stealth filler, the curing agent and the remaining solvent at a stirring speed of 800rpm for 20min to obtain component B;
[0105] (3) Mix component A and component B uniformly at a stirring speed of 500rpm for 30min to obtain the protective coating with a stealth function.
[0106] Comparative Example 4
[0107] A protective coating with a stealth function, comprising the following raw materials by weight: base resin 60 parts, stealth filler 20 parts, flame retardant 5 parts, fiber filler 8 parts, auxiliary agent 3 parts, curing agent 3 parts, and solvent 40 parts, wherein the flame retardant is aluminum hydroxide, the fiber filler is chopped glass fiber, the auxiliary agent is silane coupling agent KH-550, the curing agent is epoxy resin curing agent, and the solvent is a mixture of dimethylbenzene and butanone in a volume ratio of 7:3.
[0108] The preparation steps of the base resin are as follows: the epoxy resin and the amino silicon compound are added to toluene, stirred uniformly, the stirring speed is 200 rpm, stirring is performed for 10 min, the temperature is increased to 60 DEG C, the dibutyl tin dilaurate is added, stirring reaction is performed for 2 h, the vacuum degree is 0.03 MPa at 50 DEG C, vacuum drying is performed for 10 h, and the base resin is obtained, wherein the mass ratio of the epoxy resin, the amino silicon compound and the toluene is 2:0.5:5, the amino silicon compound is composed of N-phenyl-3-aminopropyl trimethoxysilane and aminopropyl-terminated polydimethylsiloxane with a mass ratio of 1:10, and the addition amount of the dibutyl tin dilaurate is 0.1% of the mass sum of the epoxy resin and the amino silicon compound.
[0109] The preparation of the stealth filler comprises the following steps:
[0110] Step 1, titanium aluminum carbide is dispersed in a 10wt% HF solution, etching is performed for 24 h at a temperature of 25 DEG C, ultrasonic dispersion is performed, the ultrasonic power is 100 W, the ultrasonic frequency is 40 KHz, centrifugal separation is performed at a centrifugal speed of 4000 rpm for 5 min, the supernatant is taken, and the MXene dispersion liquid is obtained, wherein the mass ratio of titanium aluminum carbide and the HF solution is 1:10;
[0111] Step 2, the N-amino-2-cyanopyrrole is mixed with the MXene dispersion liquid, the PH is adjusted to 2, ammonium persulfate is added, stirring reaction is performed for 2 h under nitrogen protection at a temperature of 5 DEG C, the stirring speed is 200 rpm, the p-phenylenediamine is added, the temperature is increased to 20 DEG C, and stirring reaction is continuously performed for 3 h, then after deionized water washing for 3 times, drying is performed at a temperature of 40 DEG C for 18 h, and the conductive composite is obtained, wherein the mass ratio of the N-amino-2-cyanopyrrole, the MXene dispersion liquid, the ammonium persulfate and the p-phenylenediamine is 4:10:0.1:0.5;
[0112] Step 3, zinc nitrate and cerium nitrate are dispersed in ethylene glycol according to a molar ratio of 1:2, wherein the amount of the ethylene glycol is 5 times of the total mass of the zinc nitrate and the cerium nitrate, then the mixture is transferred to a high-pressure reaction kettle, reaction is performed for 12 h at 180 DEG C, filtration and deionized water washing are performed for 3 times, and drying is performed at 60 DEG C for 8 h, and the core-shell structure particle is obtained;
[0113] Step 4, the conductive composite and the core-shell structure particle are mixed according to a mass ratio of 10:3, and the stealth filler is obtained.
[0114] A preparation method of a protective coating with a stealth function, comprising the following steps:
[0115] (1) the base resin, the flame retardant, the fiber filler, the auxiliary agent and 1 / 2 volume of solvent are pre-mixed and dispersed at a stirring speed of 200 rpm for 20 min and at a stirring speed of 800 rpm for 30 min, to obtain component A;
[0116] (2) The stealth filler, curing agent and remaining solvent are pre-mixed and dispersed at a stirring speed of 800 rpm for 20 min to obtain component B;
[0117] (3) Components A and B are uniformly mixed at a stirring speed of 500 rpm for 30 min to obtain the protective coating with a stealth function.
[0118] Comparative Example 5
[0119] A protective coating with a stealth function comprises the following raw materials by weight: 60 parts of base resin, 20 parts of stealth filler, 5 parts of flame retardant, 8 parts of fiber filler, 3 parts of additive, 3 parts of curing agent, and 40 parts of solvent, wherein the flame retardant is aluminum hydroxide, the fiber filler is chopped glass fiber, the additive is silane coupling agent KH-550, the curing agent is epoxy resin curing agent, and the solvent is a mixture of dimethylbenzene and butanone in a volume ratio of 7:3.
[0120] The preparation steps of the base resin are as follows: epoxy resin and amino silicon compound are added to toluene, stirred uniformly, the stirring speed is 200 rpm, stirring for 10 min, the temperature is raised to 60℃, dibutyltin dilaurate is added, stirring for 2 h, vacuum drying at 50℃ and a vacuum degree of 0.03 MPa for 10 h to obtain the base resin, wherein the mass ratio of epoxy resin, amino silicon compound and toluene is 2:0.5:5, the amino silicon compound is composed of N-phenyl-3-aminopropyl trimethoxysilane and aminopropyl-terminated polydimethylsiloxane in a mass ratio of 1:10, and the addition amount of dibutyltin dilaurate is 0.1% of the mass sum of the epoxy resin and the amino silicon compound.
[0121] The preparation of the stealth filler includes the following steps:
[0122] Step 1, disperse titanium aluminum carbide in a 10wt% HF solution, etch at a temperature of 25℃ for 24 h, ultrasonic dispersion, ultrasonic power 100 W, ultrasonic frequency 40 KHz, centrifugal separation, centrifugal speed 4000 rpm, centrifugal for 5 min, take the supernatant, obtain MXene dispersion, wherein the mass ratio of titanium aluminum carbide and HF solution is 1:10;
[0123] Step 2, the conductive polymer monomer, p-phenylenediamine and MXene dispersion liquid are mixed, the pH is adjusted to 2, ammonium persulfate is added, stirring is carried out under nitrogen protection at a temperature of 5℃ for 2h, the stirring speed is 200rpm, the temperature is increased to 20℃, and stirring is continued for 3h, then precipitation separation, deionized water washing 3 times, drying at a temperature of 40℃ for 18h, to obtain the conductive composite, wherein the mass ratio of the conductive polymer monomer, MXene dispersion liquid, ammonium persulfate and p-phenylenediamine is 4:10:0.1:0.5, the conductive polymer monomer is composed of 3,4-vinyl dioxothiophene and N-amino-2-cyanopyrrole with a mass ratio of 5:1;
[0124] Step 3, zinc nitrate and cerium nitrate are dispersed in ethylene glycol according to a molar ratio of 1:2, wherein the amount of ethylene glycol is 5 times the total mass of zinc nitrate and cerium nitrate, transferred to a high-pressure reaction kettle, reacted at 180℃ for 12h, filtered, deionized water washed 3 times, and dried at 60℃ for 8h to obtain core-shell structure particles;
[0125] Step 4, the conductive composite and the core-shell structure particles are mixed according to a mass ratio of 10:3 to obtain the stealth filler.
[0126] A preparation method of a protective coating with stealth function, comprising the following steps:
[0127] (1) The base resin, flame retardant, fiber filler, auxiliary agent and 1 / 2 volume of solvent are stirred at a speed of 200rpm for 20min, then stirred at a speed of 800rpm for 30min to carry out pre-mixing and dispersion, and component A is obtained;
[0128] (2) The stealth filler, curing agent and remaining solvent are stirred at a speed of 800rpm for 20min to carry out pre-mixing and dispersion, and component B is obtained;
[0129] (3) The components A and B are mixed uniformly, and stirred at a speed of 500rpm for 30min to obtain the protective coating with stealth function.
[0130] Performance test
[0131] The protective coating with stealth function prepared in Examples 1-3 and Comparative Examples 1-5 of the present application is coated on an aluminum alloy substrate with a coating thickness of 200μm, and dried at room temperature for 72h to obtain a protective coating with stealth function, and the performance of the coating is detected, as follows:
[0132] Adhesion: tested according to the national standard GB / T 1720-2020 “Paint film circle test”;
[0133] Weather resistance: tested according to national standard GB / T 1865-2009 "Paints and varnishes - Artificial weathering and artificial radiative exposure - Filtered xenon-arc radiation";
[0134] Flame retardant property: tested according to national standard GB 14907-2018 "Fire retardant coating for steel structure";
[0135] Electromagnetic wave absorption property: tested according to national military standard GJB 2038A-2011 "Reflectivity test method for radar wave absorbing materials";
[0136] The test results are shown in Table 1 below.
[0137] Table 1 Performance parameters of the stealth functional protective coating prepared in Examples 1-3 and Comparative Examples 1-5
[0138]
[0139] As shown by the data in Table 1 above, the stealth functional protective coating prepared in the present application has excellent performance, and has excellent stealth performance and long-term environmental stability through the multiphase synergistic design of the base resin-stealth filler-flame retardant. The coating has a coating adhesion of 1 level, no cracking and blistering after 800h weather resistance, a fire resistance limit of ≥120min, and a reflection loss of ≤-20 dB in the frequency range of 2-18 GHz. The coating can simultaneously meet the requirements of radar stealth, fire safety and complex climate resistance, and is suitable for cross-environment protection of high-value equipment such as warplanes and ships.
[0140] The specific embodiments are merely an explanation of the present application, and are not a limitation of the present application. Those skilled in the art can make modifications to the embodiments without creative contribution after reading the present specification, and the modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A protective paint with a stealth function, characterized in that, The raw materials include the following components by weight: 60-80 parts of base resin, 20-40 parts of stealth filler, 5-10 parts of flame retardant, 8-10 parts of fiber filler, 3-8 parts of auxiliary agent, 3-5 parts of curing agent, and 40-50 parts of solvent; The preparation steps of the base resin are as follows: the epoxy resin and the amino silicon compound are added into toluene, stirred uniformly, heated to 60-80 DEG C, the catalyst is added, stirred for 2-4 hours, vacuum dried, and the base resin is obtained; The mass ratio of the epoxy resin, the amino silicon compound and toluene is 2-3:0.5-1:5-10; the amino silicon compound is composed of N-phenyl-3-aminopropyl trimethoxysilane and aminopropyl-terminated polydimethylsiloxane with a mass ratio of 1-3:10-12; the addition amount of the catalyst is 0.1-1% of the mass sum of the epoxy resin and the amino silicon compound; The preparation of the stealth filler includes the following steps: Step 1, dispersing titanium aluminum carbide in HF solution, etching for 24-48 hours at a temperature of 25-30 DEG C, ultrasonic dispersion, centrifugal separation, taking the supernatant, and obtaining MXene dispersion liquid; Step 2, mixing the conductive polymer monomer with the MXene dispersion liquid, adjusting the pH to 2-3, adding ammonium persulfate, stirring for 2-3 hours under nitrogen protection at a temperature of 5-10 DEG C, adding p-phenylenediamine, heating to 20-30 DEG C, and continuing to stir for 3-5 hours, and then precipitating, washing, and drying to obtain a conductive composite; Step 3, dispersing zinc nitrate and cerium nitrate in ethylene glycol according to a molar ratio of 1-1.2:2-3, reacting for 12-14 hours at 180-200 DEG C, filtering, washing, and drying to obtain core-shell structure particles; Step 4, mixing the conductive composite and the core-shell structure particles according to a mass ratio of 10-12:3-4 to obtain the stealth filler.
2. The stealth function-possessed protective paint according to claim 1, wherein, The mass ratio of the conductive polymer monomer, the MXene dispersion liquid, ammonium persulfate and p-phenylenediamine in step 2 is 4-5:10-12:0.1-0.4:0.5-1.
3. The stealth function-possessed protective paint according to claim 1, wherein, The conductive polymer monomer in step 2 is composed of 3,4-vinyl dioxothiophene and N-amino-2-cyanopyrrole with a mass ratio of 5-8:1-3.
4. The stealth function-possessed protective paint according to claim 1, wherein, The flame retardant is one or more of aluminum hydroxide, magnesium hydroxide, magnesium oxide, and zinc borate.
5. The stealth function-possessed protective paint according to claim 1, wherein the protective paint is applied to the surface of a vehicle. The fiber filler is one or more of chopped high-silica fiber, chopped glass fiber, chopped quartz fiber, and mullite fiber.
6. The stealth function-possessed protective paint according to claim 1, wherein, The auxiliary agent is one or more of coupling agent, leveling agent, and defoaming agent; the curing agent is an epoxy resin curing agent; and the solvent is a mixture of dimethylbenzene and butanone with a volume ratio of 7:
3.
7. A method for preparing the stealth function protective coating according to any one of claims 1 to 6, characterized in that, The method includes the following steps: (1) pre-mixing and dispersing the base resin, the flame retardant, the fiber filler, the auxiliary agent, and 1 / 2-2 / 3 volume of solvent to obtain component A; (2) pre-mixing and dispersing the stealth filler, the curing agent, and the remaining solvent to obtain component B; (3) mixing component A and component B uniformly to obtain the protective coating with stealth function.
Citation Information
Patent Citations
Integrated skin capable of achieving heat shielding, heat insulation and stealth and preparation method of integrated skin
CN109532143A
Coating with stealth, heat insulation and heat protection functions as well as preparation method and application of coating
CN117106372A
Conductive polymer coated MXene-SiC-high polymer composite fiber wave-absorbing material and preparation method thereof
CN114874752A
Polyformaldehyde coating based on ferrocenyl polymer coated MXene composite material as well as preparation method and application of polyformaldehyde coating
CN116162373A